1992
DOI: 10.1002/anie.199203511
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of C60 with Dimethyldioxirane—Formation of an Epoxide and a 1,3‐Dioxolane Derivative

Abstract: Not an oxygen‐bridged annulene (structural type 1) but rather an epoxide (structural type 2) is the product of the reaction of dimethyldioxirane with C60. In a competing reaction, a 1,3‐dioxolane (structural type 3) is formed—probably by a diradical mechanism. Cleavage of acetone from 3 leading to 2 was not observed at temperatures up to 110°C. Compound 3 could provide access to ring‐opened fullerenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(72 citation statements)
references
References 37 publications
4
68
0
Order By: Relevance
“…In 1992, Creegan et al [14] synthesized C 60 O by ultraviolet (UV)-induced oxidation of a C 60 in benzene and proposed a closed [6,6] epoxide structure for it. In the same year, Elemes et al [20] reported epoxidation of C 60 with dimethyldioxirane to generate the epoxide C 60 O. Moreover, there appeared to be some experimental evidence [21,22] for the formation of more than one C 60 O isomer, for instance, Hao et al [22] reported an observation of two C 60 O isomers ( [6,6] closed and [5,6] open) in the UV-vis spectra of products from ozonization of C 60 .…”
mentioning
confidence: 97%
“…In 1992, Creegan et al [14] synthesized C 60 O by ultraviolet (UV)-induced oxidation of a C 60 in benzene and proposed a closed [6,6] epoxide structure for it. In the same year, Elemes et al [20] reported epoxidation of C 60 with dimethyldioxirane to generate the epoxide C 60 O. Moreover, there appeared to be some experimental evidence [21,22] for the formation of more than one C 60 O isomer, for instance, Hao et al [22] reported an observation of two C 60 O isomers ( [6,6] closed and [5,6] open) in the UV-vis spectra of products from ozonization of C 60 .…”
mentioning
confidence: 97%
“…Fe(ClO 4 ) 3 is an excellent reagent to promote free radical reactions of C 60 . In this article, radical reactions of C 60 promoted by Fe(ClO 4 ) 3 have been reviewed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Itami's group reported the functionalization of N-tosyl [1,2]aziridino [60]fullerene with p-tolylboronic acid in the presence of trifluoromethanesulfonic acid to afford the corresponding fullerenyl boronic esters [15]. This was the only known examples of fullerene-diol protected boronic ester.…”
Section: Reactions Of C 60 With Arylboronic Acidsmentioning
confidence: 92%
See 2 more Smart Citations